The Role of Uzbek Folk Instruments in the Educational Process - Olimov Sherali Botirovich (International Journal on Integrated Education, 2022)
This article is dedicated to the issue of Uzbek folk instruments, which gives them specific characteristics that affect the aesthetic education of students.